TEORI PERMAINAN DENGAN PURE STRATEGY PADA PERSAINGAN PRODUK MOBILE NETWORK OPERATOR - Debora Exaudi Sirait (MES: Journal of Mathematics Education and Science, 2026)
This research aims to analyze the competitive strategies between Telkomsel and XL SIM card products using game theory. The research data were obtained through questionnaires distributed to students of FMIPA as respondents. The analyzed attributes include starter card price, call and SMS tariffs, signal quality, offered features, internet access capability, active/grace period, and prize lottery programs.The validity test results show that all attributes are valid, while the reliability test produces a Cronbach’s Alpha value of 0.71, indicating that the instrument is reliable. The analysis was conducted using a payoff matrix with pure strategies through the maximin and minimax approaches. The results show that the maximin and minimax values are equal, namely 20, indicating the existence of an equilibrium point (saddle point). The optimal strategy obtained is (X3, Y5), where Telkomsel uses the signal quality strategy and XL uses the internet access capability strategy.